2020
DOI: 10.1097/phm.0000000000001626
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive Flexion Reflex Threshold in Chronic Pain Patients

Abstract: Background The nociceptive flexion reflex is a physiological, polysynaptic reflex triggered by a nociceptive stimulus activating a withdrawal response. In chronic musculoskeletal-related pain conditions, a decreased nociceptive flexion reflex threshold has been suggested as a possible recognition evidence for central sensitization that may cause alteration of central nervous system processing. Objective The aim of the study was to systematically review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…This may suggest that reduced spinal nociception after conservative interventions is limited to patients in whom enhanced spinal nociception has been demonstrated. 4,23 Furthermore, the observed NFR area inhibition seemed to be the result of the effects of TMS, whereas biofeedback training, tsDCS, and nNVS seemed to contribute little to the significant NFR area inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may suggest that reduced spinal nociception after conservative interventions is limited to patients in whom enhanced spinal nociception has been demonstrated. 4,23 Furthermore, the observed NFR area inhibition seemed to be the result of the effects of TMS, whereas biofeedback training, tsDCS, and nNVS seemed to contribute little to the significant NFR area inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…If research in chronic pain patients shows the NFR to be modulated by conservative therapy, we do not know whether this modulation can be attributed to the therapy or by enhanced spinal nociception (measured through decreased NFR thresholds and increased temporal summation of the NFR) that has already been demonstrated in this population. 4,52 Second, it might be clinically relevant to investigate whether the NFR is modifiable by conservative therapy in healthy people. For example, it might be interesting to know whether interventions aiming to promote a healthy lifestyle would be capable of modifying the NFR.…”
Section: Quantitative Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…What implied NFR-T assessment as considerable method for investigating OIH is that decreased NFR-T correlated with hyperexcitability of the central nervous system in patients with chronic pain. 47 Furthermore, multiple studies have reported a decreased threshold in patients with secondary hyperalgesia. 48 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…This reflex transmits nociceptive information from sensory receptors to spinal cord interneurons, leading to contraction of flexor muscles on the stimulated side and relaxation of extensors, facilitating escape from the stimulation. The NWR threshold, an objective measure of pain perception, is widely utilized to assess analgesic efficacy and elucidate pain mechanisms (Neziri et al, 2010) and has been associated with chronic pain (Amiri et al, 2021; Biurrun Manresa et al, 2011). stimulating the cervical vagus nerve branch, which also influences the trigeminal nerve, raises uncertainty about whether confined vagus nerve stimulation yields comparable effects.…”
Section: Introductionmentioning
confidence: 99%